Notas críticas sobre el aprendizaje estético - Pablo García Andreva (Universidad de La Rioja, 2013)
The present essay is a reflection concerning aesthetics as one of the main factors that organize the patterns of social conscience. An approach to the influence of plastic arts (which are the reference of creative activity that coordinates emotional and intellectual aspects of child's education) will show us the importance embedded in the fact of intervening in the learning of a balanced and aesthetic judgement.